JUDUL dalam PENELITIAN KUALITATIF dan CONTOHNYA - Zamsiswaya; Agus Rifai (STKIP Subang, 2026)
The research title is an essential component of scientific writing because it serves as both the identity of a study and an initial representation of its focus, scope, and direction. However, many students still encounter difficulties in formulating research titles that comply with scientific and methodological standards, particularly in qualitative research. Therefore, this study aims to describe the concept of qualitative research titles, explain the characteristics of effective research titles, and provide examples of qualitative research titles that align with methodological principles. This study employs a descriptive qualitative approach using a library research method. Data were collected through documentation studies of relevant books, journal articles, and other scholarly sources, and were analyzed using content analysis techniques. The findings indicate that a qualitative research title should clearly reflect the research focus, be concise, specific, and free from ambiguity, while remaining consistent with the research problems and objectives. Furthermore, a well-formulated title should represent the object of study, research context, and methodological approach employed. In conclusion, the ability to formulate an appropriate research title constitutes a crucial initial step in determining the quality and success of qualitative research.